Interaction between dislipidaemia, atherosclerosis of carotid artery and cognitive impairment in discirculatory encephalopathy - A. F. Vasilenko; N. S. Artyomova; Yu. S. Shamurov (Бюллетень сибирской медицины)
107 patients with discirculatory encephalopathy were examined. The main syndromes of the disease were a mild cognitive impairment, vascular parkinsonism, pseudobulbar, ataxia. Сorrelations between level cholesterol, lipoproteids low density in the blood with extent of atherosclerosis in the carotid artery and cognitive functions were analysed. The presence of atherosclerotic plaques, not thicking of intima-media complex, correlates with changes of memory and attention.